2017
DOI: 10.1039/c7dt00606c
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational circular dichroism and single crystal X-Ray diffraction analyses of [Ir(bzq)2(phen)]+ (bzq = benzo[h]quinoline; phen = 1,10-phenanthroline): absolute configuration and role of CH–π interaction in molecular packing

Abstract: Vibrational circular dichroism (VCD) spectra are measured for dichloromethane solutions of the resolved enantiomers of [Ir(bzq)(phen)] (bzqH = benzo[h]quinoline; phen = 1,10-phenanthroline). The absolute configuration of each enantiomer is determined by comparing the experimental and theoretical spectra. The result is in accord with the results of the X-ray single crystallographic analysis on the enantiomeric crystal. Moreover, the importance of the CH-π interaction is derived between phen and a hydrogen atom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…To assign the Δ, Λ isomers unambiguously, vibrational circular dichroism (VCD) spectra were further recorded and compared with those of Ru-acac . VCD spectral analysis has been effective in determining chirality, including Δ, Λ isomerism. The VCD spectra of Ru-Br 1 trop , Ru-Br 2 trop , and Ru-Br 3 trop (Figures S17–S20) are consistent with those of Δ, Λ- Ru-acac , , confirming the assignments of Δ, Λ chirality based on the ECD spectra. Finally, we verified the absolute configuration of the strongly retained fraction of Ru-Br 1 trop (Λ isomer) by single-crystal X-ray diffraction study.…”
Section: Resultssupporting
confidence: 56%
“…To assign the Δ, Λ isomers unambiguously, vibrational circular dichroism (VCD) spectra were further recorded and compared with those of Ru-acac . VCD spectral analysis has been effective in determining chirality, including Δ, Λ isomerism. The VCD spectra of Ru-Br 1 trop , Ru-Br 2 trop , and Ru-Br 3 trop (Figures S17–S20) are consistent with those of Δ, Λ- Ru-acac , , confirming the assignments of Δ, Λ chirality based on the ECD spectra. Finally, we verified the absolute configuration of the strongly retained fraction of Ru-Br 1 trop (Λ isomer) by single-crystal X-ray diffraction study.…”
Section: Resultssupporting
confidence: 56%
“…[19,86] Nevertheless, there are a number of successful theoretical studies based on molecular clusters being reported. [19,[87][88][89][90][91][92][93][94][95][96][97][98][99][100] Especially for the simpler achiral space groups this approach seems feasible. P2 1 , for instance, contains only two molecules per unit cell, which is straightforwardly translated into a cluster by adding a few more molecules to mitigate the boundary effects.…”
Section: Methodsmentioning
confidence: 99%
“…It is also the finite size effects, the distortion of cluster geometry upon structure optimisation and the introduction of unsaturated non‐covalent interactions that result in biased absorption frequencies and wrong VCD signs [19, 86] . Nevertheless, there are a number of successful theoretical studies based on molecular clusters being reported [19, 87–100] . Especially for the simpler achiral space groups this approach seems feasible.…”
Section: Vibrational Circular Dichroism (Vcd) Theorymentioning
confidence: 99%
“…Using tridentate ligands, Soloshonok et al prepared binuclear nickel­(II) complexes like 95 with a ridge-tile-like chiral topology and characterized the bended structure using VCD . Studies on luminescent transition metal complexes such as 96 or 97 benefited from the additional structural insights obtained from VCD spectroscopy as well. Chiral rhenium complexes such as 98 , have been of interest in studies on parity violations.…”
Section: Demonstrating the Diversity Of Ac Determinations Carried Out...mentioning
confidence: 99%